The Impact of Demographic, Socio-economic and Behavioral Characteristics on Attitudes Toward Credit Cards in Macedonia - Shuleska, Anita Ciunova (Mediterranean Journal of Social Sciences, 2012)
Credit cards have become an important part of everyday life without which lot of people can not imagine their life. The aim ofthis paper is to reveal the demographic, socio-economic and behavioral differences in credit cards attitudes in Macedonia. First, attitudestoward payment cards were examined by employing factor analysis. The reliability of the scale was examined using the Cronbach’ alpha.The respondents were administered the 12-item version of the credit card attitude scale and asked questions regarding theirdemographic, socio-economic and behavioral characteristics. ANOVA test was used to reveal the gender and age (demographic)differences, income and household type (socio-economic) differences and behavioral (number of credit cards owned, period ofownership, payment of balance and usage frequency) differences in components of credit cards attitudes. The results of factor analysisidentified three subscales of short credit card attitude scales while ANOVA showed significant gender and frequency of use differenceson all three credit cards attitude components, whereas other demographic, socio-economic and behavioral factors showed significantdifferences on some of the components of the attitudes toward credit cards. Recommendations presented in this research may fostergrowth of Macedonian credit card usage and help banks, financial and non-financial institutions in designing their marketing strategies.